UPAYA MENINGKATKAN PRESTASI BELAJAR BAHASA INDONESIA DALAM MATERI MEMBACA DENGAN METODE ROLE PLAYING DI KELAS XI SEKOLAH LUAR BIASA NEGERI SUKANAGARA KABUPATEN CIANJUR - Uce Solihati (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2021)
Child with Intelectual Disability (ID) is a child below average intelligence, experiences behavioral obstacles, adjustments and occurs during his development. Childrens with Intellectual Disability are often equated with mentally retardation terms (Feeble Minded). Reading using the role playing method is one of the main lessons that teachers give to children at school. The lesson, which is a part of Bahasa course, is given early as a basis for further learning. Children who cannot read yet have difficulty following other lessons. The purpose of this classroom action research is entitled